2020
DOI: 10.1111/dth.14595
|View full text |Cite
|
Sign up to set email alerts
|

Generalized pustular psoriasis following COVID ‐19

Abstract: Generalized pustular psoriasis is a rare manifestation of psoriasis that can be triggered by a variety of factors including viral infections, drugs, and the rapid tapering of systemic corticosteroids. 1 Herein, we report the case of a 60-year-old male patient who presented to the hospital on 3 July 2020, with vomiting, diarrhea, myalgia, and cough. The past medical history included hypertension, osteopenia, and subacute thyroiditis. The nasal swab polymerase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 6 publications
1
29
1
1
Order By: Relevance
“…Patients with psoriatic disease should be aware that infection with SARS-CoV-2 may result in a flare of psoriasis, including pustular flares (guidance 5.6). [74][75][76][77][78][79][80][81] Patients with psoriatic disease who become infected with SARS-CoV-2 should follow Centers for Disease Control and Prevention guidance on home isolation and discuss with their health care providers when they can end home isolation (guidance 5.7; Version 1, Supplemental Table IX available via Mendeley at https://doi.org/10.17632/w5m8jf94m8. 2).…”
Section: Category 4: What Should Patients With Psoriatic Disease Do Tmentioning
confidence: 99%
“…Patients with psoriatic disease should be aware that infection with SARS-CoV-2 may result in a flare of psoriasis, including pustular flares (guidance 5.6). [74][75][76][77][78][79][80][81] Patients with psoriatic disease who become infected with SARS-CoV-2 should follow Centers for Disease Control and Prevention guidance on home isolation and discuss with their health care providers when they can end home isolation (guidance 5.7; Version 1, Supplemental Table IX available via Mendeley at https://doi.org/10.17632/w5m8jf94m8. 2).…”
Section: Category 4: What Should Patients With Psoriatic Disease Do Tmentioning
confidence: 99%
“…Since the start of the COVID-19 pandemic, numerous cases of psoriasis flares have been reported [2][3][4] . Both viral infection and medications used for treatment, like hydroxychloroquine, were incriminated 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Though, it can also be triggered or aggravated by virus infections, especially rhinoviruses and coronaviruses 1 . SARS-CoV-2, the virus that causes coronavirus disease 2019 (COVID19), is associated with flares of psoriasis in patients with well-documented disease [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that rhinovirus and coronavirus are the most frequently detected pathogens in acute psoriasis flares after established respiratory virus infection [ 18 ]. There have been some case reports regarding the onset and exacerbation of psoriasis after COVID-19 infection [ 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Risk Factors For the Exacerbation Of Psoriasis And Covid-mentioning
confidence: 99%